Rifted margin of Rodinia revealed from airborne gravity in interior East Antarctica - T. A. Jordan; F. Ferraccioli; ARMADILLO, EGIDIO; BOZZO, EMANUELE (2010)
The existence of the Rodinia supercontinent is widely accepted, although the distribution of its constituent cratons and mobile belts and the process and timing of its break-up remain hotly debated. Several models predict that Rodinia break-up involved Neoproterozoic rifting between formerly juxtaposed East Antarctica and Laurentia. However, the paucity of geophysical exploration has hampered tracing Neoproterozoic rifting in East Antarctica, adding uncertainty to Rodinia reconstructions. We interpret new airborne gravity data to reveal the crustal architecture of the Neoproterozoic rifted margin of Rodinia in East Antarctica. A linear, ~900 km long, positive Airy isostatic gravity anomaly is recognised along the western edge of the Wilkes Subglacial Basin. Gravity and magnetic models reveal a ~10 km thick mafic body emplaced along the leading edge of the Precambrian craton, beneath interpreted Neoproterozoic rift basins. We infer that voluminous mid-crustal(?) mafic magmatism accompanied Rodinia break-up in this part of East Antarctica, and was perhaps coeval with the more weakly magmatic Adelaide Rift Complex in Australia and with continental rifts and mantle-plume related magmatism in South China.